DIVINE HELP FOR »MOONSTRUCK« MODESTUS: silver lamella for epilepsy from the ancient city of Tlos in Lycia and its archaeological context - Korkut, Taner (Jahrbuch für Antike und Christentum, 2024)
The thin ›leaf‹ (Lat. lamella, Greek πέταλον, λεπίς) of inscribed silver presented here was recently found rolled up in a bronze tubular capsule among the discarded debris of the excavated Parliament building at Tlos, Lycia, in southwestern Turkey (Anatolia), a city with a rich archaeological history. Of 3rd (or early 4th) century date, the Greek text preserves a spell exorcising a »wicked spirit« from the body of Modestus, the bearer of the amulet. The owner, also called ὁ σεληνιάζομενος, is therefore said to be suffering from the »moonstruck« disease, an uncommon description for epilepsy found, inter alia, in the gospel of Matthew (Mt. 4,24; 17,15), with which this text is compared as invaluable Hintergrund to the pagan, Jewish, and modestly Biblical ancestry of the spell, the textual antecedents of which may reach back to as early as the 1st century CE. A single anachronistically placed vanquishing ›cross‹-formula, atop the amulet, is also compared to the slogan »By this (cross) conquer«, championed by Constantine the Great on the eve of his famous battle at the Milvian Bridge in 312 CE, a battle, as it were, for all of Christendom. But the Tlos amulet, otherwise entirely non-Christian, is rather more noteworthy for its Semitic-based divine names, formulas, and language, not to speak of a non-Septuagintal citation of Gen. 1,2c. The spell was clearly the product of a text mediated by early Jewish exorcists and magoi (cf. Act. 19,13).